Pemikiran Ekonomi Islam Al-Syaibani Tentang Aktivitas Produksi - Ahmad Riyansyah; Muhammad Arifin Lubis (AGHNIYA : Jurnal Ekonomi Islam, 2021)
This study aims to analyze Al-Syaibani's Islamic economic thought about production activities. The problem to be discussed is how to implement Al-Syaibani's thinking in the benefits of production for human activities and welfare. This qualitative research has a descriptive analytical method by conducting a literature review. The results of the research obtained are that Al-Syaibani's thinking emphasizes microeconomic problems, so that his thoughts discuss in detail how the economic role of human production activities is to obtain wealth. Al Syaibani interprets that the purpose of production activity is important to play a role in bringing humans closer to God and to support the obedience so that production activities must be carried out or even required.